Legal Implications of the Practice of Selling Food Products Past the Expiration Date - Sumito; Hardyansah, Rommy; Issalillah, Fayola; Vitrianingsih, Yeni; Herisasono, Adi (Journal of Social Science Studies, 2023)
The oversight of expiration date food products is an important issue in keeping consumer health. BPOM has an important role in enforcing regulations related to food products, but there are still obstacles in oversight that cause expired products to remain in circulation. This research examines the legal implications of the practice of selling expired food products and the oversight conducted by Food and Drug Monitoring Agency (BPOM). Based on Law Number 18 Year 2012 on Food, food products that have passed the expiration date may not be sold. BPOM is authorized to withdraw products that do not meet standards and sanction violating business actors. Challenges in oversight that are limited in resources and a wide scope of oversight are problems that need to be overcome. This research proposes to increase the effectiveness of oversight through technology and training for business actors. With better oversight and increased awareness of business actors, it is expected that consumer protection against expired food products can be maximized.